3D‐Printed Multidrug‐Eluting Stent from Graphene‐Nanoplatelet‐Doped Biodegradable Polymer Composite. Issue 11 (21st March 2017) - Misra, Santosh K.; Ostadhossein, Fatemeh; Babu, Ramya; Kus, Joseph; Tankasala, Divya; Sutrisno, Andre; Walsh, Kathleen A.; Bromfield, Corinne R.; Pan, Dipanjan
Abstract : Patients with percutaneous coronary intervention generally receive either bare metal stents or drug‐eluting stents to restore the normal blood flow. However, due to the lack of stent production with an individual patient in mind, the same level of effectiveness may not be possible in treating two different clinical scenarios. This study introduces for the first time the feasibility of a patient‐specific stenting process constructed from direct 3D segmentation of medical images using direct 3D printing of biodegradable polymer–graphene composite with dual drug incorporation. A biodegradable polymer–carbon composite is prepared doped with graphene nanoplatelets to achieve controlled release of combinatorics as anticoagulation and antirestenosis agents. This study develops a technology prototyped for personalized stenting. An in silico analysis is performed to optimize the stent design for printing and its prediction of sustainability under force exerted by coronary artery or blood flow. A holistic approach covering in silico to in situ–in vivo establishes the structural integrity of the polymer composite, its mechanical properties, drug loading and release control, prototyping, functional activity, safety, and feasibility of placement in coronary artery of swine. Abstract : The feasibility of a patient‐specific stenting process constructed from computed tomographic images is introduced. A biodegradable polymer–carbon composite is prepared, doped with graphene nanoplatelets to achieve controlled release of combinatorics as anticoagulation and antirestenosis agents. A technology prototyped for personalized stenting is developed.